The idioms and its Role in making the contemporary institutional lexicon - Shbani, Bana (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research paper aimed to study the idioms lexicalization in medium sized monolingual dictionaries as an attempt to combine theorization and practice of contemporary lexicography. Theorization, or the theoretical part of the research, is dedicated to study idioms definition, aspects and types. To achieve this target, the paper focuses on the theoretical aspect of idioms regarding institutional lexicons (collaborative work) as exemplified in al-Muʿğam al-Wasīṭ of Cairo Academy of the Arabic Language. The paper depends on studying individually collected lexicons of Al- Munğid by Louis Maʿlūf as applied examples on the practical level.